Teatr Narodowy na Pomorzu w kontekście toruńskiej drogi do wolności - Artur Duda (Pamiętnik Teatralny, 2018)
The author discusses the history of Toruń’s The National Theatre in Pomerania in the context of political events (the regaining of independence by Poland, the Paris Peace Conference, the Polish-Soviet War) and the Polish-German relations just after the First World War. He describes the futile attempts made by the German authorities and directors of the Stadtheater Thorn, and Roman Kalkowski in particular, to keep a German-speaking stage in the town, and discusses the Toruń and Bydgoszcz performances of the touring Polski Theatre headed by Ludwik Dybizbański. He also focuses on the birth of the first Polish public theatre in Toruń and the most significant artistic and non-artistic events of its operation under Franciszek Frączkowski (1920/1921 season) and Mieczysław Szpakiewicz (1921/1922 season).